Titanium Fiber Plates for Bone Tissue Repair. Issue 4 (7th December 2017) - Takizawa, Takashi; Nakayama, Noboru; Haniu, Hisao; Aoki, Kaoru; Okamoto, Masanori; Nomura, Hiroki; Tanaka, Manabu; Sobajima, Atsushi; Yoshida, Kazushige; Kamanaka, Takayuki; Ajima, Kumiko; Oishi, Ayumu; et al.
Abstract: Titanium plates are widely used in clinical settings because of their high bone affinity. However, owing to their high elastic modulus, these plates are not suitable for bone repair since their proximity to the bone surface for prolonged periods can cause stress shielding, leading to bone embrittlement. In contrast, titanium fiber plates prepared by molding titanium fibers into plates by simultaneously applying compression and shear stress at normal room temperature can have an elastic modulus similar to that of bone cortex, and stress shielding will not occur even when the plate lies flush against the bone's surface. Titanium fibers can form a porous structure suitable for cell adhesion and as a bone repair scaffold. A titanium fiber plate is combined with osteoblasts and shown that the titanium fiber plate is better able to facilitate bone tissue repair than the conventional titanium plate when implanted in rat bone defects. Capable of being used in close contact with bone for a long time, and even capable of promoting bone repair, titanium fiber plates have a wide range of applications, and are expected to make great contributions to clinical management of increasing bone diseases, including bone fracture repair and bone regenerative medicine. Abstract : Titanium fiber plates prepared by molding titanium fibers into plates by simultaneously applying compression and shear stress at normal room temperature can have a Young's modulus similar to that of bone cortex, and stress shielding will not occur. Titanium fibers can form a porous structure suitable for cell adhesion and as a bone‐repair scaffold.